A Contemporary Medicolegal Analysis of Outpatient Medication Management in Chronic Pain. (November 2017) - Abrecht, Christopher R.; Brovman, Ethan Y.; Greenberg, Penny; Song, Ellen; Rathmell, James P.; Urman, Richard D.
Abstract : BACKGROUND: Opioids are frequently used in chronic pain management but are associated with significant morbidity and mortality in some patient populations. An important avenue for identifying complications—including serious or rare complications—is the study of closed malpractice claims. The present study is intended to complement the existing closed claims literature by drawing on claims from a more recent timeframe through a partnership with a large malpractice carrier, the Controlled Risk Insurance Company (CRICO). The goal of this study was to identify patient medical comorbidities and aberrant drug behaviors, as well as prescriber practices associated with patient injury and malpractice claims. Another objective was to identify claims most likely to result in payments and use this information to propose a strategy for reducing medicolegal risk. METHODS: The CRICO Strategies Comparative Benchmarking System is a database of claims drawing from >350, 000 malpractice claims from Harvard-affiliated institutions and >400 other academic and community institutions across the United States. This database was queried for closed claims from January 1, 2009, to December 31, 2013, and identified 37 cases concerning noninterventional, outpatient chronic pain management. Each file consisted of a narrative summary, including expert witness testimony, as well as coded fields for patient demographics, medical comorbidities, the alleged damaging event, the alleged injurious outcome, the total financial amount incurred, and more. We performed an analysis using these claim files. RESULTS: The mean patient age was 43.5 years, with men representing 59.5% of cases. Payments were made in 27% of cases, with a median payment of $72, 500 and a range of $7500–$687, 500. The majority of cases related to degenerative joint disease of the spine and failed back surgery syndrome; no patients in this series received treatment of malignant pain. Approximately half (49%) of cases involved a patient death. The use of long-acting opioids and medical conditions affecting the cardiac and pulmonary systems were more closely associated with death than with other outcomes. The nonpain medical conditions present in this analysis included obesity, obstructive sleep apnea, chronic obstructive pulmonary disease, hypertension, and coronary artery disease. Other claims ranged from alleged addiction to opioids from improper prescribing to alleged abandonment with withdrawal of care. The CRICO analysis suggested that patient behavior contributed to over half of these claims, whereas deficits in clinical judgment contributed to approximately 40% of the claims filed. CONCLUSIONS: Claims related to outpatient medication management in pain medicine are multifactorial, stemming from deficits in clinical judgment by physicians, noncooperation in care by patients, and poor clinical documentation. Minimization of both legal risk and patient harm can be achieved by carefully selecting patients for chronic opioid therapy and documenting compliance and improvement with the treatment plan. Medical comorbidities such as obstructive sleep apnea and the use of long-acting opioids may be particularly dangerous. Continuing physician education on the safest and most effective approaches to manage these medications in everyday practice will lead to both improved legal security and patient safety.